2013
DOI: 10.1007/s11420-013-9334-z
|View full text |Cite
|
Sign up to set email alerts
|

The Validity and Reliability of Preoperative Radiographic Canal Diameter Measurements of the Femur

Abstract: The AP plain radiographic measurement was found to be more accurate for determination of the canal diameter compared to the lateral radiograph. These findings confirm the utility of preoperative canal measurements in predicting the feasibility of placing a specific size intramedullary implant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…However, the incidence of Crowe type IV DDH is relatively low, and it is difficult to obtain a larger data series from a single institution. Second, the method of assessing the radiographic diameter of the femoral canal was imprecise as the femoral canal is not precisely round; however, other studies [43][44][45] have used similar approximate methods to assess the diameter of the femoral canal, and, therefore, we believe our final assessments of the contact areas and coincidence rates are valid.…”
Section: N a N A N A N A N A N A N A N A N A N A N A N A N A N Amentioning
confidence: 98%
“…However, the incidence of Crowe type IV DDH is relatively low, and it is difficult to obtain a larger data series from a single institution. Second, the method of assessing the radiographic diameter of the femoral canal was imprecise as the femoral canal is not precisely round; however, other studies [43][44][45] have used similar approximate methods to assess the diameter of the femoral canal, and, therefore, we believe our final assessments of the contact areas and coincidence rates are valid.…”
Section: N a N A N A N A N A N A N A N A N A N A N A N A N A N Amentioning
confidence: 98%
“…The intramedullary femoral guide rod can be jammed into the femoral isthmus during the process of total hip arthroplasty, and this jamming can be avoided with precise preoperative measurements regarding the diameter and location of the canal isthmus [ 5 , 6 ]. Traditional measurement methods of femoral morphology are primarily based on two-dimensional (2D) images, such as anterior-posterior (AP) X-ray films [ 2 , 7 10 ]. Compared to 2D measurement methods, Walsh et al reported that the diameter of the canal was measured more accurately using coronal computed tomography (CT) images [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Traditional measurement methods of femoral morphology are primarily based on two-dimensional (2D) images, such as anterior-posterior (AP) X-ray films [ 2 , 7 10 ]. Compared to 2D measurement methods, Walsh et al reported that the diameter of the canal was measured more accurately using coronal computed tomography (CT) images [ 10 ]. However, neither 3D geometry projected onto 2D planes nor selected CT images could accurately reflect the detailed osseous morphology of the femoral canal in 3D space; thus, the current methods are unreliable.…”
Section: Introductionmentioning
confidence: 99%
“…However, the incidence of Crowe type IV DDH is relatively low, and it is difficult to obtain a larger data series from a single institution. Second, the method of assessing the radiographic diameter of the femoral canal was imprecise as the femoral canal is not precisely round; however, other studies [43][44][45] Flowchart depicting the selection of hips to be evaluated.…”
Section: Discussionmentioning
confidence: 99%